Low-carbon transport in a developed megalopolis : the case of London - Banister, D; Hickman, R (Springer New York, 2011)
To really make an impact on tackling climate change over the longer term and even in the next 10–20 years, it is necessary to think more strategically wabout global, national and city-wide futures. One approach to thinking about trend-breaking futures is to use visioning and backcasting as a form of scenario building. This paper presents the results of a recently completed project on backcasting for transport in London, where a 60% reduction target in CO2 emission levels (on 1990 levels) has been set for the transport to 2025. This challenging target is articulated through the baseline case and two images of the future, one pushing the technology harder and the other emphasising the role of behavioural change. Over 150 individual policy measures have been grouped together into mutually supporting policy packages that are in turn assembled into clusters of policy packages to see whether the targets set can be reached. A simulation model has been developed to test the multiple pathways to achieving the targets set, given a range of potentially different priority perspectives. The difficulty of reaching the targets set can be demonstrated, even if all of the policy packages are used to a ‘high’ level of application. When international aviation is included and the expected growth in travel over the next 20 years, the impossibility of target achievement is clearly demonstrated.